Kants begreb om det radikale onde - Mortensen, Jacob P.B. (Dansk Teologisk Tidsskrift, 2012)
The article is a reading of Book One in Kant’s Religion within the Limits of Reason Alone. The main focus is the concept of radical evil, which Kant posits as a philosophical analogue to the Christian concept of Original Sin. The article unfolds the relations between the concepts that Kant uses to establish the concept of radical evil. The main point is that Kant ends up contradicting his own conceptual defi nition because he ascribes evil to the concept of freedom, which is fundamentally good. The article thus follows a peripheral and marginalized trajectory within Kantian scholarship by proposing a Kant who is inconsistent and paradoxical. Even though this ‘contradictory Kant’ ends up not explaining what he sets out to explain, the article appreciates his work for his effort to fi nd a foothold in the question concerning the problem of evil.